2014
DOI: 10.1080/07370016.2014.868730
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Obesity/Weight Gain Factors Among Black and Hispanic Pregnant Women

Abstract: This study examined the relationships between depressive symptoms and obesity/weight gain factors in 56 Black and Hispanic pregnant women and the differences in these variables between the 2 ethnic groups. Of the women, 32% were likely depressed, 66% were overweight/obese, and 45% gained excessive gestational weight. Depressive symptoms were positively correlated with prepregnancy body mass index (BMI; r = .268, p = .046), inversely related to gestational weight gain (r = -.329, p = .013), and not associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(32 reference statements)
2
8
1
Order By: Relevance
“…Our finding is not in line with a recent study among 725 women in which lower reported stress was associated with a greater chance of women achieving adequate gestational weight gain [14]. However, some previous studies also suggest that anxiety and depression may be protective of increased weight gain [15,17]. In the USA-study mentioned above, the association between anxiety and a higher adequacy of weight gain disappeared after adjustment for confounders, among which was physical activity [31].…”
Section: Interpretation Of Main Findingscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding is not in line with a recent study among 725 women in which lower reported stress was associated with a greater chance of women achieving adequate gestational weight gain [14]. However, some previous studies also suggest that anxiety and depression may be protective of increased weight gain [15,17]. In the USA-study mentioned above, the association between anxiety and a higher adequacy of weight gain disappeared after adjustment for confounders, among which was physical activity [31].…”
Section: Interpretation Of Main Findingscontrasting
confidence: 99%
“…In our study population, 23.1% of women had pre-pregnancy overweight or obesity and 20.1% and 45.0% of women experienced inadequate and excessive weight gain, respectively, which is in line with population figures [5,[31][32][33][34]. Although results of some previous studies suggested that psychological distress, depression, or anxiety during pregnancy are associated with gestational weight gain [14][15][16][17], one systematic review has reported no association [9] and a second systematic review only reported an association of depression, but not psychological distress and anxiety, with gestational weight gain [7]. Most previous studies did not define cutoffs for psychological distress to consider clinical importance and sample sizes were modest.…”
Section: Interpretation Of Main Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Studies were also performed in Europe (9%), Asia (2%) and Africa (2%). Sample sizes ranged from 56 (Shieh & Wu, 2014) to just over 600,000 (Kim et al., 2014) women and included women ranging in age from under 20 to over 40 years, with most women being within the ages of 20–29 years. Articles that were quantitatively analyzed most frequently included the racial/ethnic groups of White/Non-Hispanic White (72%), Black/Non-Hispanic Black (66%), Hispanic (45%), and Asian (20%).…”
Section: Resultsmentioning
confidence: 99%
“…Predictors of GWG include: pre-pregnancy weight; (Masho, Bishop & Munn, 2013; Rosal et al., 2016) socioeconomic status (SES); maternal health behaviours; (Ota et al., 2011; Heery et al., 2015) maternal age and parity (Vahratian, 2009). To date, the associations reported between race/ethnicity and discordant GWG have been diverse,(Shieh & Wu, 2014; Liu et al., 2014) likely a result of the variability in the definition of race/ethnicity and the social contexts in which they are examined. The revised 2009 IOM guidelines identified culture as a determinant of GWG (Rasmussen & Yaktine, 2009) but lacked systematic review evidence.…”
Section: Introductionmentioning
confidence: 99%